The Role of Motivation Mediates the Influence of Management Information Systems, Quality of Work Life, and Competence on Employee Performance at the Department of Food Security, Maritime Affairs and Agriculture, DKI Jakarta Province - Herry Krisnandi; Ira Perwati Sundaasih (Budapest International Research and Critics University, 2023)
The researcher took the title The Role of Motivation to Mediate the Influence of Management Information Systems, Quality of Work Life, and Competence on Employee Performance at the DKI Jakarta Province Food Security, Maritime Affairs and Agriculture Service. The number of samples is 150 respondents. The analytical method used is quantitative using SEM. The results of the study show that 1) SIM has a positive and insignificant effect on employee performance; 2) The quality of work life has a negative and significant effect on employee performance; 3) competence has a positive and insignificant effect on employee performance; 4) SIM has a positive and insignificant effect on motivation; 5) The quality of work life has a positive and significant effect on motivation; 6) Competence has a positive and significant effect on motivation; 7) Motivation has a positive and significant effect on employee performance; 8) Motivation failed to mediate SIM on employee performance; 9) Motivation successfully mediates the quality of work life on employee performance; 10) Motivation successfully mediates competency on employee performance.